Некоторые области применения электрического импульсного разряда в жидких средах - Курец В. И. Валерий Исаакович; Жучков А. И. Александр Иванович; Таракановский Э. Н. Эдуард Николаевич; Филатов Г. П. Геннадий Петрович (2001, 2001)
В фонде НТБ ТПУ отсутствует